ANALISIS KEBIJAKAN PENDIDIKAN DI INDONESIA - Fahmi Fahmi; Angel Rahmadani; Muhammad Ridho (TEACHER : Jurnal Inovasi Karya Ilmiah Guru, 2026)
The escalating disparity in service quality and the lack of synchronization between central and regional regulations in the implementation of the new national curriculum system underlie this scientific study. These macro issues have triggered the widespread impact of the digital divide and the ongoing disparity in the quality of basic services. The main focus of this research is specifically directed at analyzing the profound gap between the ideal aspects of regulation and the operational reality of the Independent Curriculum in Indonesia's frontier, outermost, and underdeveloped regions. The research steps were carried out systematically using a literature study method through a review of policy documents, critical reading of literature reports, and processing of secondary textual data for the 2024-2026 period. The quantitative research findings revealed structural barriers in the form of limited telecommunications infrastructure with school internet coverage below 50 percent, and an unequal distribution of teaching staff, indicated by a teacher-to-student ratio of 1 to 40. Although the flexibility of project-based learning is growing rapidly in urban areas, the achievement rate of operational targets in remote areas only ranges from 60 to 70 percent due to low teacher competency readiness. The main conclusion emphasizes that national education policy requires a holistic governance reconstruction through a cross-sectoral pentahelix approach to optimize local potential in a more inclusive manner. Accelerating the implementation of integrated blended learning methods following the latest regulations is projected to significantly reduce regional quality disparities by 20 to 30 percent, achieving equitable distribution of national human resource competencies. ABSTRAK Eskalasi disparitas kualitas layanan serta ketidaksinkronan regulasi pusat-daerah pada implementasi sistem kurikulum baru nasional melatarbelakangi kajian ilmiah ini. Masalah makro tersebut memicu meluasnya dampak digital divide dan ketimpangan mutu layanan dasar secara berkelanjutan. Fokus utama penelitian ini diarahkan secara spesifik untuk menganalisis kesenjangan mendalam antara aspek idealitas regulasi dengan realitas operasional Kurikulum Merdeka di wilayah terdepan, terluar, dan tertinggal Indonesia. Langkah-langkah penelitian dijalankan secara sistematis menggunakan metode studi pustaka melalui telaah dokumen kebijakan, pembacaan kritis laporan literatur, serta pengolahan data tekstual sekunder periode 2024-2026. Temuan penelitian kuantitatif menyingkap adanya hambatan struktural berupa keterbatasan infrastruktur telekomunikasi dengan cakupan internet sekolah di bawah 50 persen, serta timpangnya distribusi tenaga pendidik yang ditunjukkan oleh rasio guru banding siswa mencapai 1 banding 40. Meskipun fleksibilitas pembelajaran berbasis proyek berkembang pesat di area urban, tingkat ketercapaian target operasional di daerah terpencil hanya berkisar antara 60 hingga 70 persen akibat rendahnya kesiapan kompetensi guru. Simpulan utama menegaskan bahwa kebijakan pendidikan nasional memerlukan rekonstruksi tata kelola holistik melalui pendekatan lintas-sektor model pentahelix guna mengoptimalkan potensi lokal secara lebih inklusif. Akselerasi metode pembelajaran campuran terpadu pasca-regulasi terbaru diproyeksikan andal mereduksi angka ketimpangan mutu regional sebesar 20 sampai 30 persen demi mewujudkan keadilan pemerataan kompetensi sumber daya manusia nasional.